Altered N170 and mood symptoms in bipolar disorder: An electrophysiological study of configural face processing. (17th November 2017) - Tso, Ivy F; Grove, Tyler B; Mueller, Savanna A; O'Donnell, Lisa; Chun, Jinsoo; McInnis, Melvin G; Deldin, Patricia J
Abstract : Objectives: Altered social behavior during mood episodes in bipolar disorder often has detrimental and long‐lasting interpersonal consequences. Abnormal face processing may play a role in linking brain functions to clinical symptoms and behavior. This study aimed to understand configural face processing in bipolar disorder as a function of basic communicative attributes of the face and mood symptoms using event‐related brain potentials (ERPs). Methods: Forty‐two participants with bipolar I disorder (BP) and 43 healthy controls (HC) viewed face stimuli varying in emotion (neutral or fearful), head orientation (forward or deviated), and gaze direction (direct or averted) while ERPs were recorded. Configural face processing was indexed by the N170 wave. Results: BP participants had comparable overall N170 amplitude and peak latency to HC, although timing was more variable in the BP group. Abnormal N170 modulations by communicative face attributes were observed in BP: exaggerated sensitivity to emotion (fearful > neutral) in the left hemisphere, and reduced sensitivity to gaze‐head incongruency (where N170 is normally larger in response to faces with incongruent than congruent gaze and head direction) in the right hemisphere. The former was not associated with mood symptoms, suggesting a heightened trait‐like sensitivity to negative emotions. The latter was correlated with greater manic symptoms, indicating that an impaired perceptual sensitivity to faces with features signaling incongruent social attention may underlie social deficits observed during mania. Conclusions: These findings suggest a pathophysiological role of altered configural face processing in the phenomenology of bipolar disorder, and call for further investigations to evaluate its potential as a biomarker and treatment target.